Análise das inter-relações dos sinais vitais em pacientes portadores e não portadores de cardiopatia isquêmica - Pinheiro, Fernando Krein (2017)
According to the World Health Organization, cardiovascular diseases are the leading cause of death worldwide. Estimates made by the Brazilian Society of Cardiology indicate a total of 346,896 deaths from cardiovascular problems just in 2015. Cardiovascular diseases cause twice as many deaths as cancer of all kinds together; 2.3 times more than all external causes (accidents and violence); 3 times more than respiratory diseases and 6.5 times more than all infections. Faced with this situation and with the purpose of collaborating with the field of health, this study had the principal objective of estimating the interrelations of vital signs of patients with heart disease through vector autoregressive modeling (VAR) and to determine the behavior of the variables when there is an external shock in a particular system variable through the Impulse Response function. As a result, a significant difference was found in all the stages examined. Descriptive statistics showed changes between the averages in the two groups of patients analyzed, showing some degree of hypertension in cardiac patients. The lag calculus presented 3 to 4 lags of difference between cardiac and non-cardiac patients, and the estimation of a VAR (1) model captured the interrelationships between the vital signs variables, presenting different behavior in both groups. The Impulse Response function permitted identification of the changes that occur in the endogenous system variables, when an external event affects the exogenous variables, thus spreading the disturbances to all the other variables.